Epichloe novae-zelandiae, a new endophyte from the endemic New Zealand grass Poa matthewsii. Issue 4 (2nd October 2019) - Leuchtmann, Adrian; Young, Carolyn A.; Stewart, Alan V.; Simpson, Wayne R.; Hume, David E.; Scott, Barry
ABSTRACT: Epichloe endophytes (Clavicipitaceae) infect pooid grass genera worldwide but predominantly in the Northern Hemisphere, but appear to be rare in native grasses of the Southern Hemisphere. Because of benefits that hosts may receive from the symbiosis, Epichloe endophytes have been extensively studied and are considered important components of sustainable agriculture. There are only a few studies available on the incidence of endophyte infection in grasses of the Southern Hemisphere and most grass species have never been examined. Here we report on a survey of native grasses of New Zealand including 25 endemic or indigenous species. We sampled up to 10 plants per species at different sites from both the North and South Island of New Zealand and examined tissues microscopically for endophyte infection. Overall, only two species were found to be infected, Poa matthewsii (Matthew's bluegrass) and Dichelachne micrantha (short-hair plume grass). Based on analyses of tefA and tubB genes, both endophytes were found to be interspecific hybrids. The endophyte of the new host D. micrantha was previously described as Epichloe australiensis, while the endophyte of P. matthewsii is a new species named here E. novae-zelandiae . The new species is a hybrid derived from E. amarillans, E. bromicola and E. typhina subsp. poae. Alkaloid analyses in planta suggested that E. novae-zelandiae can produce small amounts of peramine, early pathway indole-diterpenes and ergot alkaloids, but no lolines or lolitrems. Target specific primers suggested the presence of genes for ergot alkaloids and peramine, but genes of only early pathway steps for the other alkaloids. Furthermore, genes for both mating type idiomorphs ( MTA and MTB ) were present, a single copy of MTA and two copies of MTB . Endophytes of native grasses may provide a genetic resource that could be exploited for developing pasture grass cultivars with improved performance.